Organizing Nursing Knowledge from Metatheoretical Structuralism's Point of View - Federico, Lucía (2023)
In the present article we will show the potential metatheoretical structuralism has to improve the mainstream proposal for organizing the scientific knowledge of nursing: namely, Jacqueline Fawcett?s structural holarchy. In order to achieve such an objective, we will start by analyzing the philosophical foundations of structural holarchy. After that we will present the structuralist proposal for organizing science through net-theories and finally we will show that the structuralist framework captures Fawcett?s intuitions but in a more precise fashion, as it is not attached to perished misconceptions inherited from the received view from philosophy of science as the structural holarchy is. A better organization of nursing science may aid nursing professionals to achieve a better epistemological status which could help them to get better budgets and the social recognition they deserve as scientific workers in the frontline of health systems.